Effects of Chronic Sleep Fragmentation on Wake-Active Neurons and the Hypercapnic Arousal Response. Issue 1 (1st January 2014) - Li, Yanpeng; Panossian, Lori A.; Zhang, Jing; Zhu, Yan; Zhan, Guanxia; Chou, Yu-Ting; Fenik, Polina; Bhatnagar, Seema; Piel, David A.; Beck, Sheryl G.; Veasey, Sigrid
Abstract: Study Objectives: Delayed hypercapnic arousals may occur in obstructive sleep apnea. The impaired arousal response is expected to promote more pronounced oxyhemoglobin desaturations. We hypothesized that long-term sleep fragmentation (SF) results in injury to or dysfunction of wake-active neurons that manifests, in part, as a delayed hypercapnic arousal response. Design: Adult male mice were implanted for behavioral state recordings and randomly assigned to 4 weeks of either orbital platform SF (SF4wk, 30 events/h) or control conditions (Ct4wk) prior to behavioral, histological, and locus coeruleus (LC) whole cell electrophysiological evaluations. Measurements and Results: SF was successfully achieved across the 4 week study, as evidenced by a persistently increased arousal index, P < 0.01 and shortened sleep bouts, P < 0.05, while total sleep/wake times and plasma corticosterone levels were unaffected. A multiple sleep latency test performed at the onset of the dark period showed a reduced latency to sleep in SF4wk mice (P < 0.05). The hypercapnic arousal latency was increased, Ct4wk 64 ± 5 sec vs. SF4wk 154 ± 6 sec, P < 0.001, and remained elevated after a 2 week recovery (101 ± 4 sec, P < 0.001). C-fos activation in noradrenergic, orexinergic, histaminergic, and cholinergic wake-active neurons was reduced in response to hypercapnia (P < 0.05-0.001). Catecholaminergic and orexinergic projections into the cingulate cortex were also reduced in SF4wk (P < 0.01). In addition, SF4wk resulted in impaired LC neuron excitability (P < 0.01). Conclusions: Four weeks of sleep fragmentation (SF4wk) impairs arousal responses to hypercapnia, reduces wake neuron projections and locus coeruleus neuronal excitability, supporting the concepts that some effects of sleep fragmentation may contribute to impaired arousal responses in sleep apnea, which may not reverse immediately with therapy.